Early stages of ZIF-8 film growth: the enhancement effect of primers exposing sulfonate groups as surface-confined nucleation agents1. Issue 90 (2nd October 2015) - Tuninetti, Jimena S.; Rafti, Matías; Azzaroni, Omar
<x xml:space="preserve">Abstract</x> We describe the use of sulfonate-terminated self-assembled monolayers as very efficient surface-confined nucleation agents for rapid growth of dense, thick and well-percolated ZIF-8 films.